The profile of a ‘perfect' invader – the case of killer shrimp, Dikerogammarus villosus - Rewicz, T.; Grabowski, M.; MacNeil, C.; Bącela-Spychalska, K. (Aquatic Invasions, 2014)
The ‘killer shrimp’, Dikerogammarus villosus, has been recognised as one of the 100 worst alien species in Europe, in terms of negative impacts on the biodiversity and functioning of invaded ecosystems. During the last twenty years, this Ponto-Caspian amphipod crustacean has rapidly spread throughout Europe’s freshwaters and its invasion and continued range expansion represents a major conservation management problem. Although a great deal of research has focused on this almost ‘perfect’ invader as its damaging impacts, realised and potential, have become evident, we now present the first comprehensive review of D. villosus taxonomy, morphology, distribution, community impacts, parasites, life history, physiological tolerance and finally, possible eradication methods. We show the direct and indirect ecosystem impacts of this invader can be profound, as it is a top predator, capable of engaging in a diverse array of other feeding modes. It can quickly dominate resident macroinvertebrate communities in terms of numbers and biomass, with subsequent large-scale reductions in local biodiversity and potentially altering energy cycling, such as leaf litter processing. This damaging European invader has the potential to become a key invader on a global scale as it may be capable of reaching North American freshwaters, such as the Great Lakes. One positive aspect of this invader’s spread and impact is increased interest in alien species research generally, from decision-makers, stakeholders and the general public. This has resulted in greater financial support to study invasion mechanisms, preventative measures to stop invasion spread and ways to minimise damaging impacts. Our review provides a specific example, that studies identifying management strategies that mitigate against a potential invader’s spread should be undertaken at the earliest possible opportunity in order to minimise potentially irreversible ecosystem damage and biodiversity loss.